Dampak Masuknya Industri Pertanian Terhadap Sosial Ekonomi Masyarakat di Kampung Wapeko Distrik Kurik - Nugraha, Raka Faza; Widiastuti, Maria Maghdalena Diana; Simatupang, David Oscar (MuJAgri: Musamus Journal of Agribusiness, 2020)
The purpose of this study is what factors significantly influence the entry of modern agriculture industry in Kampung Wapeko. The place and time of the study was carried out in Wapeko Village, Kurik District. The population in the study was 79 households. Data analysis method with Linear Regression Analysis with Binary Logistics. Results and discussion Social factors as independent variables are X1 (health quality), X2 (quality of education), X3 (community interaction). Economic factors as independent variables are X4 (family income), X5 (employment opportunities). With an error range of 5%, there are no significant variables that have an impact on the agricultural industry for the community in Kampung Wapeko. It was concluded that the entry of the modern agricultural industry did not provide an impact on the social and economic community in Kampung Wapeko Keywords: industry; agriculture; social economy